The Incidence of Repeat Breeding in Dairy Cows under Tropical Condition - M Yusuf; L Rahim; M A Asja; A Wahyudi (Media Peternakan, 2012)
The objective of this study was to investigate the incidence of repeat breeding in dairy cows under tropical condition. This was a preliminary study conducted in Sinjai Regency, Indonesia. A total of 82 Holstein Friesian lactating cows from five dairy farmer groups were used in the present study. Of the 82 cows, 75.6% eventually became pregnant after repeated inseminations (AI). The incidence of repeat breeding in this area was very high (62%). Days in milk (DIM) at first AI, first AI conception rate, and calving to conception interval were 62.5±19.3 days, 0%, and 202.8±150.0 days, respectively. There was no difference in DIM at first AI between repeat breeders and normal fertility cows (60.4±15.2 days vs 68.3±28.6 days).  However, normal fertility cows required only 123.3±52.9 days to conceive and 2.4±0.8 inseminations per pregnancy, whereas repeat breeders required significantly more days to conceive (222.9±134.1 days) and more inseminations per pregnancy (4.8±0.9). In conclusion, repeat breeder dairy cows under tropical condition had very poor and reduced reproductive performance.